Association between perineal trauma and pain in primiparous women - Adriana Amorim Francisco; Mirian Hiromi Kinjo; Caroline de Souza Bosco; Renata Luana da Silva; Edilaine de Paula Batista Mendes; Sonia Maria Junqueira Vasconcellos Oliveira (SciELO, 2014)
Objective To identify the association between perineal trauma and pain in 473 primiparous women. Method Cross-sectional study in which pain was measured by the numerical pain scale (0 to 10 - 0 being no pain and 10 maximal pain). Results The prevalence and mean intensity of pain were 33.0% and 4.7 points (standard deviation = 2.0) in the numeric scale, respectively. Episiotomy represented the most frequent trauma (46.7%). The occurrence and intensity of the pain were associated with perineal trauma and postpartum time. Having perineal trauma tripled the chance of pain. Each hour elapsed following the birth reduced the chance of pain by 4.8%. Conclusion Primiparous women are subject to a high frequency of perineal trauma, with episiotomy being the most prominent. Perineal pain affects approximately one-third of primiparous women and is associated with the postpartum time and perineal traumas.